MEDICATION CALCULATION IN NEONATES AND PEDIATRICS: DEVELOPMENT AND VALIDATION OF A MOBILE APPLICATION. - Moreno-Llanos, Angeles Haydee; Morelos-García, Edgar Noé; Lerma-Sánchez, Ángel Mario; Zamarioli, Cristina Mara; Castañeda-Hidalgo, Hortensia; Sauceda-Flores, Perla Francisca; Hernández-Herrera, Dolores Eunice (Texto & Contexto Enfermagem, 2024)
Objective: to describe the process of developing and validating a mobile application for medication dosing in neonatal and pediatric services. Method: a methodological study based on the instructional design model with 5 stages: analysis, design, development, implementation, and evaluation. The first 3 phases of development were conducted by a computer engineer. The content and appearance validity index were measured by clinical nurses (n=20) and computer systems engineers (n=18), respectively, and the usability was evaluated with nursing students (n=61). Results: after the development phase, the Matymar V 1.0 mobile app was made available on a free platform to use on the Android system. The content validity index was 1.0, while the appearance index showed variations. The usability evaluation of the app, conducted by 61 nursing students, was positive for medication dose calculations in neonatal and pediatric services. Conclusions: the model used proved effective for developing the app, which received positive evaluations from clinical nurses and systems engineers in terms of content and appearance through the concordance index validation, as well as from nursing students in the usability evaluation. It is a useful and functional app for dose calculation, transitioning from a conventional method to a technological system, making the dosing process safer, more reliable, and time-efficient.